Bacterial Contamination of Tsire-Suya, a Nigerian Meat Product - Uzeh, R.E.; Ohenhen, R.E.; Adeniji, O.O. (Pakistan Journal of Nutrition, 2006)
Samples of raw meat prior to roasting, and tsire-suya were analyzed bacteriologically for total viable, coliform, staphylococcal counts and the presence of Pseudomonas aeruginosa, Bacillus cereus, Staphylococcus aureus and Escherichia coli. The sensitivity of the bacterial isolates to some antibiotics and spices was evaluated. The total viable count varied from 20x10 2 to 289x10 2 cfu/g for the raw meat and 7x10 2 to 171x10 2 cfu/g for the tsire-suya. The coliform count was 4x10 2 to 71x10 2 cfu/g for the raw meat and 1x10 2 to 42x10 2 for the tsire-suya while the staphylococcal count ranged from 1x10 2 to 60x10 2 cfu/g for the raw meat and 1x10 2 to 12x10 2 cfu/g for tsire-suya. From results obtained, bacterial count was higher in raw meat than in tsire-suya. P. aeruginosa, B. cereus, S. aureus, and E. coli, were isolated from the raw meat and tsire-suya. The isolates were sensitive to some of the antibiotics and spices tested. However, E. coli was only sensitive to gentamicin. While P. aeruginosa on the other hand was resistant to Afromomum melegueta, Piper quinense and Capsicum fructescens, the three spices tested for this study. The incidence of the isolated bacteria in tsire-suya, a ready-to-eat meat product in Nigeria is of health significance.